ĐKXĐ : ....
PT \(\Leftrightarrow\sqrt{-x^2+4x-3}-1+\sqrt{-2x^2+8x+1}-3=x\left(x^2-4x+4\right)\)
\(\Leftrightarrow\frac{-x^2+4x-4}{\sqrt{-x^2+4x-3}+1}+\frac{-2x^2+8x-8}{\sqrt{-2x^2+8x+1}+3}=x\left(x-2\right)^2\)
\(\Leftrightarrow\frac{\left(x-2\right)^2}{\sqrt{-x^2+4x-3}+1}+\frac{2\left(x-2\right)^2}{\sqrt{-2x^2+8x+1}+3}+x\left(x-2\right)^2=0\)
\(\Leftrightarrow\left(x-2\right)^2\left(\frac{1}{\sqrt{-x^2+4x-3}+1}+\frac{2}{\sqrt{-2x^2+8x+1}+3}+x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(x-2\right)^2=0\\\frac{1}{\sqrt{-x^2+4x-3}+1}+\frac{2}{\sqrt{-2x^2+8x+1}+3}+x=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\\frac{1}{\sqrt{-x^2+4x-3}+1}+\frac{2}{\sqrt{-2x^2+8x+1}+3}+x>0\left(loai\right)\end{cases}}\)
Bạn Thanh Tùng DZ ơi sao trường hợp 2 lại loại vậy
Chưa có điều kiện của x mà